Using metadata analysis and base analysis techniques in DQ framework for DW - Abdul Aziz, Azwa; Mohd Saman, Md Yazid; Hamzah, Mohd Pouzi (2010)
Data Qualities (DQ) issues become a major concern over decade.Even with an enhancements and introduction of new technologies, it is stills not good if systems are lack of qualities of data.Data warehouses (DW) are complex systems that have to deliver highly- aggregated, high quality data from heterogeneous sources to decision makers. It involves a lot of integration of sources system to support business operations.This paper propose a framework for implementing DQ in DW systems architecture using Metadata Analysis Technique and Base Analysis Techniques to perform comparison between target value and current value gain from the systems.A prototype using PHP is develops to support Base Analysis Techniques. This paper also emphasize on dimension need to be consider to perform DQ processes.